من حلات الاسهال لدى الاطفال في محافظة الديوانيه Campylobacter jejuni عزل وتشخيص بكتريا - الغالبي احلام (University of Thi-Qar Journal of Science, 2010)
The aim of the present study was to isolate and identify of Campylobacter jejuni from some cases of children infected with watery and bloody diarrhea under age 5 years old through the period May 2007 to end of August 2007. seventy eight of samples were taken and examined to isolate Campylobacter jejuni, the results revealed isolation of 109 bacteria and 7 of them represent Campylobacter jejuni with percentage 6.4%. The bacteria were identified depending on morphological and cultural characters and with procedure some of biochemical tests. The results showed too, capability of this bacteria on production of β-lactamase enzyme. The study of drugs sensitivity to antibiotics appears absolute sensitivity to Rifampin and tetracycline and absolute resistance to ampicillin and amoxicillin and different in resistance range to gentamycin, chloramphenicol, erythromycin and cephalothin with different percentages.